$f$
is defined recursively for all integers $n>1,p>0$
as follows: $$ \begin{aligned} f(1,p) &= C + p, \\ f(n,1) &= C, \\ f(n,p) &= f(n-1, f(n,p-1)) \end{aligned} $$
where $C>0$
is a real constant. Give a non-recursive expression for $f(4,p).$
Proof is not required.
Hint: You may want to try $f(2,p)$
first.
-
Try writing out and spotting patterns in
$f(2,p).$
-
Try writing this in a non-recursive form.
-
… by noticing it is only recursive in the second argument,
$p$
(the$2$
is fixed). -
How might you do the same for
$f(3,p)?$
-
Remember to use results you’ve already shown.
-
Using the hint provided in the question, we try to find an expression for
$f(2,p).$
From the definition we get that$f(2,p) = f(1, f(2, p-1)) = C + f(2, p-1).$
Since the first argument is fixed at$2,$
we can unravel it to get$f(2,p)=C+\ldots+C+f(2,1)=C \cdot p.$
We can apply the same strategy to find
$f(3,p).$
We start with$f(3,p) = f(2, f(3, p-1)),$
at which point we use our previous result to get$f(3,p)=C \cdot f(3,p-1).$
Similarly, this unravels to$f(3,p)=C^p.$
Finally, we get to
$f(4,p) = f(3, f(4, p-1)) = C^{f(4,p-1)},$
which expands to$f(4, p) = C^{C^{\cdot^{\cdot^{\cdot^C}}}},$
which is a tower of height$p.$